(1106) Planning the Production of Consumer Goods تخطيط إنتاج السلع الاستهلاكية - Zosimov G. P. (INP., 2020)
Improvement of welfare in the working people is an objective prerequisite of increase of population goods for consumption. Under socialism , the volume of production of goods is fully subordinated to the demands of the main economic law of socialism.